2020
DOI: 10.1111/liv.14696
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in human nonalcoholic fatty liver disease: A systematic review and meta‐analysis

Abstract: Background The gut‐liver axis is considered to play a critical role in the development and progression of nonalcoholic fatty liver disease (NAFLD). The integrity of the epithelial barrier is crucial to protect the liver against the invasion of microbial products from the gut, although its exact role in NAFLD onset and progression is not clear. Methods We performed a systematic review and meta‐analysis of studies that addressed the intestinal permeability (IP) in association with NAFLD presence or severity as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 47 publications
1
48
0
5
Order By: Relevance
“…An intact intestinal barrier is able to antagonize the translocation of bacterial products, while allowing active transport of nutrients across tight junctions. As reported in a recent meta‐analysis, intestinal permeability appears to be raised in NAFLD patients, being associated with the degree of hepatic steatosis 163 . In this complex scenario, a crucial role is played by the intestinal microbiota, playing a major role in NAFLD.…”
Section: Nafld and Risk Of Cardiovascular Diseasesmentioning
confidence: 78%
“…An intact intestinal barrier is able to antagonize the translocation of bacterial products, while allowing active transport of nutrients across tight junctions. As reported in a recent meta‐analysis, intestinal permeability appears to be raised in NAFLD patients, being associated with the degree of hepatic steatosis 163 . In this complex scenario, a crucial role is played by the intestinal microbiota, playing a major role in NAFLD.…”
Section: Nafld and Risk Of Cardiovascular Diseasesmentioning
confidence: 78%
“…Also, the integrity of the mucosal barrier is essential to protect the liver against the invasion of microbial products from the intestine (De Munck et al, 2020). Generally, intestinal villus height (VH) and mucosal thickness (MT) are two essential indices and the intestinal absorptive capacity can be partly characterized by them (Manzanilla et al, 2004;Zhang et al, 2012;Zhang, Zhong, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A healthy intestine is instrumental for absorbability and utilization of nutrients from diet and a main barrier function for animals to resist various stimuli of external environment (Zheng et al., 2018). Also, the integrity of the mucosal barrier is essential to protect the liver against the invasion of microbial products from the intestine (De Munck et al., 2020). Generally, intestinal villus height (VH) and mucosal thickness (MT) are two essential indices and the intestinal absorptive capacity can be partly characterized by them (Manzanilla et al., 2004; Zhang et al., 2012; Zhang, Zhong, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the gut barrier is critical to protect the liver from the invasion of intestinal microflora. A meta-analysis found that intestinal permeability in patients with NAFLD was higher than that in healthy controls and was associated with the degree of hepatic steatosis ( De Munck et al, 2020 ). Besides, the composition of gut microbes is different between NAFLD patients and healthy people.…”
Section: Gm and Metabolic Diseasesmentioning
confidence: 99%